Union of the Comoros : First Review Under the Staff-Monitored Program and Request for Extension; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Comoros is a small, fragile island state (population: 850,000) with persistently low and shock-prone growth and a high risk of external debt distress. Officially recorded COVID-related casualties have remained low (4,569 infections and 151 deaths so far). Growth projections remain at 1.6 percent in 2021 and 3.8 percent in 2022, supported in part by progress in vaccinations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Central African Republic